EXPERIMENTAL STUDY OF MATTRESS FOUNDATION ON VERY SOFT CLAY FOR UNPAVED ROAD (GEOMATE Journal, 2025)
Soft clay subgrade contains an undrained strength ranging from 5~25 kN/m2, which is significantly low and provides inadequate support for road construction. Therefore, this study proposes a mechanical method to increase the bearing capacity within the concrete precast of local stone material used in Ternate Island, also known as a mattress. The experiment was conducted by modelling a mattress with hexapod concretes comprised of granular material, wet soil mixed with gravels, sands, and soils. The obtained component was manually compacted and used as a mattress foundation on the very soft clay for designing an unpaved road. Furthermore, empirical mathematical methods were used to determine the field CBR tests by observing the ultimate stress levels of the mattress foundation. The results showed that the hexapod mattress obtained an average CBR of 7.99% or a quom of 79.9 kN/m2, with more than 6% below the minimum standard. Based on the simulation results, CBR 6.14% and 7.99% can be used to apply static load on axle P at 40.17 kN, with a tire inflation pressure pc of 620 kN/m2, and load distribution angle α0 of 26.5 °. The predictive response of the internal friction of the mattress ϕ at 45 ° ~ 50 °, led to an ultimate minimum stress qum of 61.42 kN/m2, showing that the safety factors F0 of 1.5 to 2.1 provided unpaved h0 design thicknesses of 0.50 meters and 0.60 meters, respectively. In conclusion, very soft clay with CBR 6% and thickness h0 of 0.30 ~ 1.20m needs to be applied as a mattress foundation on unpaved roads for rill construction.